HARMONI TIGA RUMAH IBADAH: ARTIKULASI PENDIDIKAN TOLERANSI DI PONDOK PESANTREN AL-JAMHAR BALUN TURI LAMONGAN MENUJU GLOBAL HARMONY - Miftakhul Muthoharoh (LPPM STAI Ihyaul Ulum Gresik, 2025)
This study explores the articulation of tolerance education at Pondok Pesantren Al-Jamhar Balun, Turi, Lamongan, which is uniquely located alongside three houses of worship a mosque, a church, and a temple. The research aims to examine how pesantren culture and education contribute to fostering tolerance and promoting global harmony. Using a qualitative approach through observation, interviews, and documentation, the study identifies several strategies: integration of tolerance into the curriculum, habituation through daily practices, interfaith dialogue, joint social activities, and exemplary leadership by Kiai M. Ikhsan and Nyai Listiyani. Findings show that these practices cultivate mutual respect, solidarity, and inclusivity among santri and the surrounding community. The discussion highlights both achievements and challenges, such as stereotypes, literacy gaps, and external pressures, which are addressed through inclusive pedagogy and social engagement. In conclusion, Al-Jamhar functions as a local laboratory of peace education, whose values and practices have universal significance and serve as a transferable model for nurturing love, tolerance, and global harmony.